About Steps and substitutes of Don Quixote in the Entremeses of the Golden Age (ALPHA. Journal of Arts, Literature and Philosophy, 2016)
This paper reviews the different recreations of Don Quixote in the Entremeses of the seventeenth century. These recreations sometimes are treated as very simple motive mentions. However, they also function as complex texts signaling the popularity of the novel of Cervantes and his character always from a playful and festive perspective.
Keywords: Recreations; Don Quixote; Entremeses; Golden age